Flow Simulations in a Pebble Bed Reactor by a Combined DEM-CFD Approach. (1st February 2018) - Zhang, Sijun; Zhao, Xiang; Yang, Zhi
Abstract: This paper presents computational fluid dynamics (CFD) gas flow simulations within a segment of the pebble bed core. The realistic packing structure in an entire pebble bed reactor (PBR) is produced by a means of discrete element method. The packing structure in the segment of the PBR core is then obtained. The gas flow through the voids formed by the packed pebbles is computed by CFD. It is found that the packing structure of pebbles in the PBR is crucial to CFD simulation results. On the other hand, in our numerical simulations both large eddy simulation and Reynolds-Averaged Navier-Stokes models are employed to study the effects of different turbulence models on gas flow field and relevant heat transfer. The calculations indicate the complex flow structure within the voids among the pebbles, which play the key role in heat transfer predictions.